Penerapan Prinsip Prinsip Pelayanan Publik Di Bidang Pelayanan Pendaftaran Penduduk Dan Catatan Sipil Kantor Dinas Kependudukan Dan Catatan Sipil Kota Pekanbaru - Sufian Hamim; Lolita Vianda; Sella Pitaloka (UIR Press, 2020)
The purpose of the study was to analyze and explain the application of the principles of public service in the Field of Population Registration and Civil Registration Services Office of the Population and Civil Registry Office of the City of Pekanbaru. This research uses quantitative and qualitative approaches to strengthen one another. A quantitative approach to descriptive statistical analysis, with survey methods. In survey research, information was collected from 42 respondents using a questionnaire and the collection of relevant secondary data. The qualitative approach was carried out by interviewing 10 informants and observations involved to complement the quantitative approach. Overall implementation of the principles of public service in the Department of Population and Civil Registry Pekanbaru City is in the category of implemented or 36%, quite implemented or 45% and less implemented or 19%. Civil Registry Pekanbaru City, only one indicator of the principle of public service security that has been implemented well or 56%. This means that the management process feels safe, there are security guards, no fighting incidents have occurred, all applicant communities can take shelter from rain or heat because the office is quite large, it's just not comfortable because the service and waiting rooms feel cramped and noisy, while the products are legal and legal. Only one indicator of the principle of public service convenience is less well implemented or 39%. This means that public services at the Department of Population and Civil Registry of Pekanbaru City are lacking in comfort, the community feels that the service process is lacking in order, many people stand unable to sit, a bit chaotic, noisy noise and hot air temperature; office environment Not comfortable there is no green park and the office waiting room is narrow and not clean; The parking lot is narrow and cluttered, mostly using public roads; the toilets are less clean, the number of users is small, there are no prayer rooms for prayer rooms. The other eight principles of public service have been implemented quite well or 45%, namely: simplicity, clarity, time certainty, accuracy, responsibility, infrastructure, ease of access, and discipline. The indicator that is not well implemented is the principle of comfort. Therefore, in the future Pekanbaru City Population and Civil Registry Office should improve comfort in public services.